Identifying and understanding factors associated with failure to complete infantry training among British Army recruits - Kiernan, Matthew D. (2011)
BACKGROUND: Over 30% of the British Army‟s Infantry Recruits who underwent training between 1999 and 2003 failed to complete their training. Previous studies have focused predominantly on identifying the cumulative reasons for failure. There is a dearth of research investigating the effect of failure on the individual recruit and what influences their ability to pass training.